50 let konstrukcijskega inženirstva na IKPIR - Duhovnik, Janez (Gradbeni vestnik, 2021)
We present and overview of activities related to structural engineering and computational mechanics during the fifty years of existence of the Institute of Structural Engineering, Earthquake Engineering and Construction IT (IKPIR). The main research as well as other activities are briefly described.
Keywords: finite elements; IKPIR; končni elementi; konstrukcijsko inženirstvo; numerical mechanics; numerična mehanika; structural engineering